Konsep Bantuan Hukum Dalam Peradilan Pidana Di Indonesia - Suryantoro, Dwi Dasa (STAI Nurul Huda Kapongan Situbondo, 2021)
Regarding legal aid, it includes the principle of equality before the law and access to legal counsel, and in Indonesia's positive law it has been clearly and firmly regulated in various laws and regulations. In the criminal justice system in Indonesia, the regulations governing legal aid have long been contained in the Criminal Procedure Code. The concept of legal aid itself is actually not a dead concept, meaning that until now we must continuously review it, because after all there are shifts and/or developments concerning the dimensions of time, approach, social, political and economic structure, as well as local conditions. certain factors have their own influence on the study of legal aid.